Promoting male partner testing and safer sexual decision-making through secondary distribution of HIV self-tests by HIV-uninfected female sex workers and women receiving antenatal and postpartum care in Kenya: a cohort study - Thirumurthy, Harsha (Lancet HIV, 2016)
BACKGROUND: Identifying interventions to increase men’s uptake of HIV testing in sub-Saharan Africa is essential for the success of combination HIV prevention. HIV self-testing is an emerging approach with high acceptability, but limited evidence exists on optimal strategies for distributing self-tests. We explored a novel approach of providing multiple self-tests to women at high risk of HIV acquisition in order to promote partner HIV testing and facilitate safer sexual decision-making. METHODS: HIV-uninfected women aged 18–39 years were recruited at two sites in Kisumu, Kenya: a health facility with antenatal (ANC) and postpartum (PPC) clinics, and a drop-in center for female sex workers (FSW). Following informed consent and instructions on using the OraQuick Rapid HIV 1/2 Test, index participants (IPs) enrolled at the health facility and drop-in center received 3 and 5 self-tests, respectively. Structured interviews were conducted with IPs at enrollment and over 3 months to determine how self-tests were used. Key outcomes included the number of self-tests distributed by IPs, the proportion of IPs whose sexual partners used a self-test, couples testing, and sexual behavior following self-testing. FINDINGS: Between January 14, 2015 and March 13, 2015, 280 IPs were enrolled (61 ANC, 117 PPC, 102 FSW). Follow-up interviews were completed with 265 IPs (96%). Most IPs with a primary sexual partner distributed a self-test to that partner (53/58, 91% ANC; 91/106, 86% PPC; 64/85, 75% FSW). A vast majority of FSW IPs also distributed ≥1 self-tests to commercial sex clients (82/101, 81%). Among self-tests distributed to and used by IPs’ primary sexual partners, couples testing occurred frequently (27/53, 51% ANC; 62/91, 68% PPC; and 53/64; 83% FSW). Among self-tests distributed to and used by IPs’ sexual partners, an HIV-positive result was obtained for 3.8% (2/53), 2.2% (2/91), and 13.8% (41/298) of the tests in the ANC, PPC, and FSW participant groups, respectively. Sexual intercourse was significantly less likely after a sexual partner tested HIV-positive versus HIV-negative (18% vs. 62%, p<0.0001), while condom use was significantly more likely (100% vs. 44%, p=0.0018). Of 265 IPs with follow-up data, four reported intimate partner violence as a result of self-test distribution. No other adverse events were reported. INTERPRETATION: Provision of multiple HIV self-tests to women at high risk of HIV infection was successful in promoting HIV testing among their sexual partners and in facilitating safer sexual decisions. This novel strategy warrants further consideration as countries develop self-testing policies and programs.